Differences within elite female tennis players during an incremental field test - Brechbuhl, C.; Girard, O.; Millet, G. P.; Schmitt, L. (Medicine & Science in Sports & Exercise, 2018)
Purpose: To compare technical and physiological responses between junior and professional female players during an incremental field test to exhaustion specific to tennis.